Effect of different slaughtering methods on metabolites of broiler chickens using ultra high-performance liquid chromatography-time of flight-mass spectrometry (UHPLC-TOF-MS) - Ali N.S.M.; Zabidi A.R.; Manap M.N.A.; Zahari S.M.S.N.S.; Yahaya N. (Rynnye Lyan Resources, 2024)
Indexed by Scopus/ERA